PTJ Transitions - Roger Herr (Physical Therapy, 2023)
IMPORTANCE: Home health and outpatient physical therapy are important for recovery after lower extremity joint replacement (LEJR), yet their use may be influenced by social determinants of health (SDOH). OBJECTIVE: The objective of this study was to identify SDOH factors at the patient, hospital, and regional levels that are associated with the use of home health and outpatient physical therapy after LEJR. DESIGN: This cross-sectional study used 100% Medicare fee-for-service claims. Hierarchical regression models assessed associations of patient-, hospital-, and regional-level SDOH with home health and outpatient physical therapy utilization. SETTING: Not applicable. PARTICIPANTS: Medicare beneficiaries who were 66 years old and older in 2018 and who were eligible for participation in the Comprehensive Care for Joint Replacement (CJR) program. EXPOSURE(S): SDOH at the patient level (race, dual eligibility status), hospital level (percentage of Disproportionate Share Hospital patients), and regional level (themes from the Social Vulnerability Index). MAIN OUTCOME AND MEASURE(S): Number of physical therapy visits in home health and outpatient settings within 90 days after discharge following a LEJR surgery, stratified by hip replacement and knee replacement. RESULTS: This study included 74,937 patients undergoing joint replacement from January 1 to September 30, 2018. At the patient level, Black patients had more home health and outpatient physical therapy visits than White patients following both knee and hip replacement. Dual-eligibility status was associated with more home health visits but fewer outpatient physical therapy visits. At the regional level, greater socioeconomic vulnerability was associated with more home health visits and outpatient physical therapy visits. Greater vulnerability in housing type and transportation was associated with more home health visits but fewer outpatient physical therapy visits. CONCLUSIONS: SDOH were associated with greater home health and outpatient physical therapy utilization following hospital discharge after joint replacement. RELEVANCE: Incorporating SDOH into discharge planning may promote equitable access to community-based rehabilitation following LEJR.